2016
DOI: 10.1177/2055116916651649
|View full text |Cite
|
Sign up to set email alerts
|

Lungworm Eucoleus aerophilus (Capillaria aerophila) infection in a feline immunodeficiency virus-positive cat in France

Abstract: Case summaryA 2-year-old domestic shorthair female outdoor cat living in France was diagnosed with a lungworm infection due to Eucoleus aerophilus. The history and clinical signs, in association with bronchoscopic examination, suggested chronic upper respiratory disease. Cytological examination of bronchoalveolar lavage fluid (BALF) was consistent with suppurative bronchitis. Direct microscopic examination of BALF enabled the identification of E aerophilus ova.Relevance and novel informationThe cat was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Finally, epidemiological studies reporting the prevalence of respiratory trichuroid nematodes in cats have been performed in Albania, Denmark, Germany, Hungary, Italy, Poland, Portugal, Romania and Spain; our results for E. aerophilus (6.2%) are similar to the highest prevalences reported (8.2%) in Europe (Capári et al., 2013 ; Genchi et al., 2021 ; Hansen et al., 2017 ; Krone et al., 2008 ; Knaus et al., 2014 ; Mircean et al., 2010 ; Miró et al., 2004 ; Tamponi et al., 2017 ; Traversa et al., 2009 ; Waap et al., 2014 ; Wierzbowska et al., 2020 ). In addition, this parasite has also been identified in domestic cats from other European countries such as France, Hungary, Greece, Belgium and Lithuania (Elhamiani‐Khatat, Rosenberg, Benchekroun & Polack, 2016 ; Haralampides, 1978 ; Rehbein et al., 2014 ; Thienpont et al., 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, epidemiological studies reporting the prevalence of respiratory trichuroid nematodes in cats have been performed in Albania, Denmark, Germany, Hungary, Italy, Poland, Portugal, Romania and Spain; our results for E. aerophilus (6.2%) are similar to the highest prevalences reported (8.2%) in Europe (Capári et al., 2013 ; Genchi et al., 2021 ; Hansen et al., 2017 ; Krone et al., 2008 ; Knaus et al., 2014 ; Mircean et al., 2010 ; Miró et al., 2004 ; Tamponi et al., 2017 ; Traversa et al., 2009 ; Waap et al., 2014 ; Wierzbowska et al., 2020 ). In addition, this parasite has also been identified in domestic cats from other European countries such as France, Hungary, Greece, Belgium and Lithuania (Elhamiani‐Khatat, Rosenberg, Benchekroun & Polack, 2016 ; Haralampides, 1978 ; Rehbein et al., 2014 ; Thienpont et al., 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for aelurostrongylosis and troglostrongylosis, laboratory findings are of limited interest. Leukocytosis accompanied with eosinophilia and monocytosis are frequently described, as in many other feline respiratory diseases [ 8 , 46 ].…”
Section: Clinical Knowledgementioning
confidence: 99%
“…Knowledge of radiographic alterations in feline pulmonary capillariosis is even more fragmentary. Recent studies have indicated that X-ray alterations vary from absent [ 46 ] to combinations of bronchial, interstitial and alveolar patterns [ 8 , 47 ]. Two recent series, although on a small number of cases, have also shown that a bronchial pattern is almost invariably present in cats infected with C. aerophila, often associated with alveolar and/or interstitial patterns (unstructured or nodular) [ 8 , 47 ].…”
Section: Clinical Knowledgementioning
confidence: 99%
“…Upon hatching in the intestines, the larvae migrate via the bloodstream to the upper respiratory tract. Infection with E. aerophilus is commonly asymptomatic, with young animals infected with a heavy burden or co-infected with other pathogens, usually those resulting in immunosuppression – such as Feline Immunodeficiency Virus (FIV) and Addison’s disease – most likely to display clinical signs ( Barrs et al., 2000 ; Burgess et al., 2008 ; Elhamiani Khatat et al., 2016 ; Crisi et al., 2017 ; Morelli et al, 2021a ). Clinical signs are non-specific and include generalized respiratory distress, wet to dry coughing, sneezing, wheezing and nasal discharge accompanied by lethargy, fever, depression and weight loss ( Traversa et al, 2009a , 2010 ; Crisi et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%